A function-oriented surface reconstruction framework for reverse engineering. Issue 1 (2021) - Qie, Yifan; Bickel, Sebastian; Wartzack, Sandro; Schleich, Benjamin; Anwer, Nabil
Abstract: Reverse engineering can be considered as the methodological process of analyzing and reconstructing a digital model of a physical asset. It has gained considerable interest with the advent of sophisticated sensors and data processing technologies hence becoming an important enabler for the product digital twin. However, while existing approaches to reverse engineering focus on the mere geometric reconstruction, this paper presents a novel paradigm called function-oriented surface reconstruction, that is capable of reconstructing the underlying part and surface function and thus outperforms existing methods. The applicability of the presented method is demonstrated through a case study of a gearbox.